## Recommended Posts

Excuse asking this here but I can't get my head around this:

x = y-(0.38196601*(y-(0.61803399*y)))

If we know the value for x (say x = 3) what is the formula to calculate y ???? ##### Share on other sites

Excuse asking this here but I can't get my head around this:

x = y-(0.38196601*(y-(0.61803399*y)))

If we know the value for x (say x = 3) what is the formula to calculate y ???? Ok stig here's what I have: from what I understand the issue here is that they are trying to confuse you with the notation making it all look crazy therefore we will substitute the scary numbers for the beginning with letter.

so:

I unnderstand that your * = multiplication

and you have x = 3

then we substitute:

0.38196601 = a

0.6180399 = b

so we will have

x = y - a(y-by)

which becomes

x = y - ay + aby

x = y(-a+ab)

now all you have to do is calculate what's in the parethesis

which in you case

0.38196601 = a

0.6180399 = b

so you get x = y(-0.38196601+0.6180399*0.38196601)

and you get smth like x = y(-0.145895775376201)

then you replace x with 3 like you said

so 3 = y(-0.145895775376201)

so

y = 3 / -0.145895775376201

y = 20.562624190209210767200795911796

Since I'm in a rush I didn't verify any calculation but that should be the way to solve it.

I hope it helps

##### Share on other sites

I think this got it LOL sorry.

http://www.intmath.com/Basic-algebra/Algeb...blem-solver.php

3=y-(0.382)(y-0.618y)

Since y is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.

y-(0.382)(y-0.618y)=3

Since y and -0.618y are like terms, add -0.618y to y to get 0.382y.

y-(0.382)(0.382y)=3

Multiply 0.382 by 0.382y to get 0.146y.

y-(0.146y)=3

Multiply -1 by the 0.146y inside the parenthesis.

y-0.146y=3

Since y and -0.146y are like terms, add -0.146y to y to get 0.854y.

0.854y=3

Divide each term in the equation by 0.854.

Cancel the common factor of 0.854.

Divide 3 by 0.854 to get 3.512.

y=3.512

Edited by mwight

##### Share on other sites

0.38196601 = a

0.61803399 = b Missed 3

so we will have

x = y - a(y-by)

which becomes

x = y - ay + aby

x = y(-a+ab) Wrong. It's x = y*(1-a+ab)

x = y*(1-a+ab)

0.38196601 = a

0.61803399 = b

x=y*(1 - 0.38196601 + 0.38196601 * 0.61803399)

x=y*(0.61803399 + 0.38196601 * 0.61803399)

x=3

y=3 / (0.61803399 * 1.38196601)

y=3 / 0.854101967

y=3.51246118

Something like that

Edited by Smile

##### Share on other sites

LOL Not yet fellas I am creating a logarithmic sequence of which I knew the upper limit, i.e y = 39.900

Using the formula x = y-(0.38196601*(y-(0.61803399*y)))

We get x = 34.079

At each subsequent step downt the scale the previous x becomes the new y (i.e. 34.079 becomes y and so on) this scale goes down as such:

39.900 34.079 29.107 24.860 21.233 18.135 15.489 13.229 11.299 9.651 8.243 7.040 6.013 5.136 4.386 3.746 3.200

Now what I want to be able to do is to allocate a lower parameter value (3.200 for example) and calculate the scale from the bottom up. Cheers

x = y*(1-a+a* 0.38196601 = a

0.61803399 = b

x=y*(1 - 0.38196601 + 0.38196601 * 0.61803399)

x=y*(0.61803399 + 0.38196601 * 0.61803399)

x=3

y=3 / (0.61803399 * 1.38196601)

y=3 / 0.854101967

y=3.51246118

Something like that

YAYAYAYAYAYYAYAYA!!!!!!! That's it.

******* BIG HUGS FOR SMILE **********        Thanks champ I owe you one.

##### Share on other sites

LOL Not yet fellas I am creating a logarithmic sequence of which I knew the upper limit, i.e y = 39.900

Using the formula x = y-(0.38196601*(y-(0.61803399*y)))

We get x = 34.079

At each subsequent step downt the scale the previous x becomes the new y (i.e. 34.079 becomes y and so on) this scale goes down as such:

39.900 34.079 29.107 24.860 21.233 18.135 15.489 13.229 11.299 9.651 8.243 7.040 6.013 5.136 4.386 3.746 3.200

Now what I want to be able to do is to allocate a lower parameter value (3.200 for example) and calculate the scale from the bottom up. Cheers

YAYAYAYAYAYYAYAYA!!!!!!! That's it.

******* BIG HUGS FOR SMILE **********        Thanks champ I owe you one.

Hi! May my math of Yin-Yang Symbol will also be interesting for you: My Webpage

##### Share on other sites

Stigweard, you're welcome. Stalker, welcome to Taobums. About time you migrated here from HT forum. Take it easy on Russian news though. ##### Share on other sites

here:

x = y-(0.38196601*(y-(0.61803399*y)))

x= y-(.381*(y-.618y)) -->subtract (1-.618)

x= y-(.381*(.381y)) --> multiply .38196601 * .38196601 = .145898032

x= y-.145y --> subtract 1-.145 = .85410196

x= .845y

y=x/.85410196

substitute values for x to solve for y.

##### Share on other sites

x = y*(1-a+ab)

0.38196601 = a

0.61803399 = b

x=y*(1 - 0.38196601 + 0.38196601 * 0.61803399)

x=y*(0.61803399 + 0.38196601 * 0.61803399)

x=3

y=3 / (0.61803399 * 1.38196601)

y=3 / 0.854101967

y=3.51246118

WTF?

o.k. it's not THAT bad, but we wonder why we can't understand Drew 